Aprendizaje de sistema de ecuaciones lineales y geogebra en estudiantes del vi ciclo de Educación Secundaria - Poicon Cornejo, Hanai Miluska (2022)
The objective of the research was to determine the relationship between the learning of the system of equations and GeoGebra in students of the VI cycle of secondary education of the San Antonio María Claret Educational Institution. The research is of a correlational type, with a non-experimental, transactional correlational design; whose sample consisted of 35 students, to whom the questionnaires were applied both for learning the system of equations and for GeoGebra. According to the results of the Rho Spearman statistical test, the hypothesis of the proposed research has been confirmed, with a 95% probability and a 5% margin of error: There is a direct and significant relationship between the learning of the system of equations and GeoGebra in students of the VI cycle of secondary education. The conclusion reached was that there is a direct and significant relationship between the learning of the system of equations and GeoGebra, with a coefficient of Rho = 0.663 and a p value of 0.000.